Assessing Responses of Functional Resistance Training on Selected Body Composition Variables Among Female Students - Jithin Das T K; Albert Chandrasekar, Sigamani Jayasingh; K V, Sooryajith; Maneesha Abraham (Physical Education Theory and Methodology, 2025)
Objectives. This study aimed to examine the responses of incorporating functional resistance training program and to ascertain the impact of this structured program on body composition variables among female students. Materials and methods. For this study, 20 interested female students (age: 22.15 ± 1.95 years) from the SRM IST in Kattankulathur, Chennai, were selected as participants. After baseline measurements, participants were randomized into training (n = 10) and control (n = 10) groups. The experimental group engaged in an 8-week training program comprising40–60 minutes of low-to-moderate intensity functional resistance training. Body composition variables such as weight, BMI, and waist-hip ratio were chosen as dependent variables for the study. To assess the baseline group differences,independent sample t-tests were used. Intervention effects were examined by paired sample t-tests to determine within-group effect of college students, including body weight, BMI and WHR. The significance level was set at 0.05. Results. The paired sample t-test showed a significant difference (p < 0.05) in body composition among the experimental group. The pre and post-test values were considerably different (p < 0.05) in the training group. According to the findings, it was revealed that functional resistance program led to marked decreases (p < 0.05) in weight, BMI and WHR. However, no substantial differences were found in the control group. Conclusions. The study concluded that after eight weeks of engaging in FRT programme, significant improved responseswere observed in body composition variables such as weight, BMI, and waist-hip ratio among female students.